2014
DOI: 10.1177/1362480614526276
|View full text |Cite
|
Sign up to set email alerts
|

Studying the community corrections field: Applying neo-institutional theories to a hidden element of mass social control

Abstract: The growth in US incarcerated populations has produced unintended negative consequences for other justice system agencies. The community corrections field is faced with two related problems stemming from prison growth: (1) significant growth in populations under supervision and (2) populations with higher needs for service. I apply a theoretical framework adapted from organizational sociological research to address change and stasis as isomorphic processes. Criminologists rarely situate the community correctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Building off pioneering work on parole (e.g. Simon, 1993) and intermediate sanctions (Morris & Tonry, 1991), scholars are beginning to investigate “mass social control,” particularly the expansion of community sanctions (DeMichele, 2014). Critical to this movement has been work on “mass supervision” in Europe and beyond (Robinson, McNeill & Maruna, 2012).…”
Section: The Punitive Turn and Probationmentioning
confidence: 99%
“…Building off pioneering work on parole (e.g. Simon, 1993) and intermediate sanctions (Morris & Tonry, 1991), scholars are beginning to investigate “mass social control,” particularly the expansion of community sanctions (DeMichele, 2014). Critical to this movement has been work on “mass supervision” in Europe and beyond (Robinson, McNeill & Maruna, 2012).…”
Section: The Punitive Turn and Probationmentioning
confidence: 99%
“…Any defective products of the criminal justice system would be those of re-offending offenders and dissatisfied victims (Benard, Paoline, & Pare, 2005). Thus, the shared goals among professionals across components of the criminal justice as well as shared goals among administrative-level and line corrections personnel has the potential to improve reentry success (Bernard et al, 2005;DeMichele, 2014;Gibbs, 1970;Giblin, 2013;Kraska & Brent, 2011;National Research Council;.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this reason, electronic monitoring in Europe is not a uniform sanction type, but there are signs of convergence. Specifically, Kalmthout and Durnescu's () review of European probation showed a general trend toward policies derived from the Anglo‐Saxon model, which emphasizes correction and control more than rehabilitation and social welfare (for a discussion of penal organizational isomorphism across contexts, see DeMichele, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the increase in mass social control—mass imprisonment paralleled by mass probation, as observed in the United States (Phelps, )—is unprecedented in a Danish context. Also, the parallel trends of increased use of community supervisions and increased social control from the early 1980s onward in the United States (DeMichele, ) are not found in Denmark, at least not to the same degree, despite the recent emergence of “tough‐on‐crime” policies (for a general introduction to the Scandinavian penal justice systems, see Lappi‐Seppälä and Tonry, ).…”
Section: Introductionmentioning
confidence: 99%